"Stress taper" fixation increases torsional failure strength in a cadaveric femur model. (April 2022) - Raducha, Jeremy E.; Nacca, Christopher R.; Crisco, Joseph J.; Evans, Andrew R.
Abstract: Background: To potentially limit peri-implant fractures our institution commonly implements a "stress-taper" fixation construct in which the screw lengths towards the proximal end of a construct are incrementally decreased, in order to avoid a focal stress-riser when loaded. To assess this construct, we asked: 1) Does the stress taper strategy increase torsional strength than the bicortical locking construct when biomechanically tested in a cadaveric femur model? 2) Does it fail in a less comminuted fracture pattern? Methods: Seven matched pairs of cadaveric femora were randomly assigned to one of two distal femur fixation groups: plating with stress taper strategy or bicortical fixation. Specimens were first cyclically loaded, then axially rotated to failure under 800 N of compression. Peak torque at failure, degrees of rotation at failure, and energy to failure were calculated and compared using paired t -tests. Fractures were categorized with the assistance of fluoroscopy according to the Orthopedic Trauma Association classification, 32. Findings: There was significantly greater peak torque (110.6 ± 49.7 Nm vs. 80.6 ± 35.2 Nm), rotation at failure (23.8 ± 5.3° vs 18.9 ± 4.5°) and energy to failure (25.3 ± 15.7 J vs. 14.1 ± 8.3 J) in the stress-taper group as compared to the bicortical group ( p = 0.0424), ( p = 0.0213) and ( p = 0.0460), respectively. 6/7 fractures in the stress-taper group were classified 32 A1 with 1/7 classified A2. 5/7 fractures in the bicortical group were classified B1 and 2/7 classified A2. Interpretation: ' Stress taper fixation' in distal femurs may be protective against peri-implant fractures compared to traditional bicortical fixation. The 'stress taper' concept can increase torsional failure strength in an in vitro model. Highlights: The stress taper is an alternate fixation construct for distal femur fractures. The stress taper dissipates the stress riser at the proximal aspect of the plate. The stress taper demonstrated greater torque, rotation and energy at failure. Stress taper fixation may be protective against peri-implant fractures.